KEPEMIMPINAN KIAI DALAM MENGINTERNALISASI KARAKTER MODERAT: TINJAUAN FENOMENOLOGI KETOKOHAN KIAI SUBAGION - Lukman Hakim Mustaqim, Aziz; Komalia, Isti; Rasit Sah, Moh; Yani, Ahmad (CV. Lafadz Jaya, 2025)
This study examines the role of kiai leadership in internalizing moderate character within the pesantren environment, focusing on the figure of Kiai Subagion. Utilizing a phenomenological approach, the research aims to understand how Kiai Subagion, as a spiritual and social leader, instills moderate values in his students through his actions, teachings, and personal example. The analysis includes the challenges faced during the internalization of these values, particularly in the context of evolving social dynamics. The findings are expected to provide new insights into the influence of kiai leadership in shaping moderate character and its effectiveness in managing diversity and differences within society. This study is significant in understanding how moderation values are taught and adopted in pesantrens as a model for conflict resolution and social tolerance enhancement.